Effects of TiO2 phase and nanostructures as photoanode on the performance of dye-sensitized solar cells - Muqoyyanah, Muqoyyanah (Springer, 2021)
In this study, different titanium dioxide (TiO2) nanostructures and phase were investigated as photoanode film for application in dye-sensitized solar cells. Rutile TiO2 nanorods (NRs)-nanotrees (NTs) and TiO2 NRs-microcauliflowers (MCFs) were synthesized via hydrothermal method for different time. The mixed phase of rutile-anatase film was fabricated by applying TiO2 nanoparticles paste on the synthesized TiO2 NRs-NTs via squeegee method. The counter electrode film was fabricated by spraying deposition and sputtering methods of reduced graphene oxide–multi-walled carbon nanotubes and platinum, respectively. Solar simulator measurement revealed that higher energy conversion efficiency (1.420%) and short-circuit current density (3.584 mA cm-2) were achieved by using rutile TiO2 NRs-MCFs film. The utilization of a thick rutile film with microparticle structures increases dye adsorption, and thus enhances the electron excitation. Graphic abstract: [Figure not available: see fulltext.].